Studying the diffusion of responsibility in relation to stock market non-participation - Thöni, Sylvain (Student Undergraduate Research E-journal!, 2019)
In the light of the equity premium, stock market nonparticipation remains a puzzling phenomenon. Policy makers seeking to address non-participation, by providing investment advice, might however crowd out informal financial advisors due to the bystander effect; the inverse relation between the number of actors able to provide aid and the actual readiness of any individual to provide aid. A between subject survey was used to test willingness to give financial advice based on the presence of bystanders. Employing Mann-Whitney tests and a logit regression model, I find that the presence of bystanders does lower individual tendency to give financial advice.